2006
DOI: 10.1017/s1138741600005916
|View full text |Cite
|
Sign up to set email alerts
|

Is there any Relationship between Sexual Attraction and Gender Typology?

Abstract: People can be classified as attracted to both sexes, to men, to women, or to neither sex, and also as instrumental-expressive, instrumental, expressive, or non-instrumental-expressive. The two hypotheses tested herein are, on the one hand, the relative independence between these two typologies and, on the other, the close relation between sexual dimorphism and sexual attraction, in contrast to the relative independence between sexual dimorphism and the instrumental and expressive domains. A total of 503 univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Both scales (Attraction to Women and Attraction to Men) obtained satisfactory internal consistency, with Cronbach's alpha values of .98. Concerning construct validity, the results of factor analyses supported both the inversely related bidimensionality and the bipolar unidimensionality (Fernández, Quiroga , & Del Olmo, 2006;Fernández, Quiroga, & Rodríguez, 2006). The Bem Sex Role Inventory (BSRI, Bem, 1974).…”
Section: Instrumentsmentioning
confidence: 86%
See 1 more Smart Citation
“…Both scales (Attraction to Women and Attraction to Men) obtained satisfactory internal consistency, with Cronbach's alpha values of .98. Concerning construct validity, the results of factor analyses supported both the inversely related bidimensionality and the bipolar unidimensionality (Fernández, Quiroga , & Del Olmo, 2006;Fernández, Quiroga, & Rodríguez, 2006). The Bem Sex Role Inventory (BSRI, Bem, 1974).…”
Section: Instrumentsmentioning
confidence: 86%
“…If it was possible to develop a relatively well-founded instrument-the SAQ-based on sexology, surely a better instrument than the BSRI could be developed based on genderology, which could operationalize the instrumental and expressive traits, defined with precision and scientifically based. The consideration of these two quite diverse realities-sex and gender-leads to better understanding of people's development, both from the sexual outlookattracted to both sexes, to neither, to men, or to womenand from the outlook of the instrumental and expressive traits-instrumental and expressive, instrumental, expressive, and non-instrumental-expressive-without the one substituting or encompassing the other (Fernández, Quiroga, & Del Olmo, 2006). From the standpoint of autonomy and independence, in order to understand the complex reality of sexed and gendered individuals, both entities must be complementary.…”
Section: Fernández Quiroga and Del Olmomentioning
confidence: 99%
“…The starting point of this approach is apparent sexual dimorphism, whose explanatory mechanisms are relatively well-known. These authors showed that (a) men and women from all societies are capable of differentiating sexual dimorphism with no difficulty, even from a very early age; (b) a high percentage of men feel sexual attraction to women, just as women are attracted to men; (c) some percentage of men and women display dual attraction (towards both sexes); (d) some percentage are attracted to people of the same sex; and (e) a minimal percentage of men and women display no apparent sexual attraction towards either of the sexes (Busseri, Willoughby, Chalmers, & Bogaert, 2008;D'Augelli & Patterson, 2001;Diamond, 1993;Fernández, Quiroga, & Del Olmo, 2006a, 2006bLippa, 2007;Omoto & Kurtzman, 2006). Considering the large percentage of men attracted to women and of women attracted to men, in our time and our societies, these authors infer that sexual attraction can be operationalized by means of two clusters of items, defined either as a function of the object of attraction (attraction to women and to men), or as the specificity of their content (thoughts-cognitive aspect-, feelings-emotional aspect-, behaviors-observable FERNÁNDEZ, QUIROGA, DEL OLMO, BUIZZA, AND IMBASCIATI aspect,-and social image-hetero-appraisal aspect).…”
mentioning
confidence: 99%
“…Romantic relationships may be described as mutual and intimate relationships that exist between two people, thereby facilitating love, affection, and sexual intimacy (Fernández, Quiroga, & Del Olmo, 2006). Romantic relationships create bonds between the partners involved and facilitates financial, emotional, and psychological commitment.…”
mentioning
confidence: 99%
“…Nonetheless, the advent of social media may have enhanced sharing, receiving, and accessing pornographic contents with minimal limitations (González-Ortega, Vicario-Molina, Martínez, & Orgaz, 2015), thereby creating further concerns about the phenomenon. Romantic relationships may be described as mutual and intimate relationships that exist between two people, thereby facilitating love, affection, and sexual intimacy (Fernández, Quiroga, & Del Olmo, 2006). Romantic relationships create bonds between the partners involved and facilitates financial, emotional, and psychological commitment.…”
mentioning
confidence: 99%